Global consensus on nutritional rickets: Implications for Australia. (22nd June 2020) - Siafarikas, Aris; Simm, Peter; Zacharin, Margaret; Jefferies, Craig; Lafferty, Antony R; Wheeler, Benjamin J; Tham, Elaine; Brown, Justin; Biggin, Andrew; Hofman, Paul; Woodhead, Helen; Rodda, Christine; et al.
Abstract : In 2016, a global consensus on the prevention, diagnosis and management of nutritional rickets was published. The bone and mineral working group of the Australasian Paediatric Endocrine Group provides a summary and highlights differences to previous Australian and New Zealand (ANZ) guidelines on vitamin D deficiency and their implications for clinicians. Key points are: (i) The International Consensus document is focused on nutritional rickets, whereas the ANZ guidelines were focused on vitamin D deficiency. (ii) Definitions for the interpretation of 25‐hydroxy vitamin D (25OHD) levels do not differ between statements. (iii) The global consensus recommends that routine 25OHD screening should not be performed in healthy children and recommendations for vitamin D supplementation are not based solely on 25OHD levels. The Australasian Paediatric Endocrine Group bone and mineral working group supports that screening for vitamin D deficiency should be restricted to populations at risk. (iv) Recommendations from the global consensus for vitamin D dosages for the therapy of nutritional rickets (diagnosed based on history, physical examination, biochemical testing and a confirmation by X‐rays) are higher than in ANZ publications. (v) The global consensus recommends the implementation of public health strategies such as universal supplementation with vitamin D from birth to 1 year of age and food fortification. We conclude that updated global recommendations for therapy of nutritional rickets complement previously published position statements for Australia and New Zealand. Screening, management and the implementation of public health strategies need to be further explored for Australia.